ANALISIS DETERMINAN HIPERTENSI PADA PASIEN DI PUSKESMAS :LITERATUR REVIEW - Abidah, Siti; Evi Fatmi Utami; Hardani; Nur Atikah (Pharmaceutical and Traditional Medicine, 2020)
Hypertension is a circulatory system disorder that causes an increase in pressure blood above normal, which is 140/90 mmHg. Hypertensive disease gives continuous symptoms for a target organ, such as stroke for muscles, coronary heart disease for blood vessels. Symptoms continued in hypertensive patients can be reduced by analyzing the determinants of hypertension in patients. The purpose of this study was to determine the risk factors for hypertension in patients ini Public health center This research is type of literature review research by collecting data in the form of articles and theses through google scholar s?tus with years between 2012-2019. So that the literature is obtained as many as seven journals and two theses. The results of this study indicate that statistically the variables that were significantly related to the incidence of hypertension were genetics, age, gender, obesity, alcohol, and consumption of salty foods. But there is one finding from various variables studied such as genetics, gender, alcohol, and consumption of salty foods which stated that there was no relationship between these variables and the incidence of hypertension, surgical results obtained can be caused by differences in research design, number and type of sample, lifestyle and research location. The factors that are not proven to be risk factors for hypertension are the consumption of fatty foods and stress.